Development and Use of a Polyvalent Conjugate to Differentiate Histoplasma capsulatum and Histoplasma duboisii from Other Pathogens - Kaufman, Leo (1968)
Previous investigations have demonstrated the existence of five Histoplasma capsulatum serotypes. Available specific fluorescent-antibody reagents stain only four of the five serotypes. Antibodies produced against the most complete H. capsulatum serotype were labeled with fluorescein isothiocyanate to develop a reagent specific for H. capsulatum that was reactive with all the known serotypes. The unadsorbed reagent not only stained all the H. capsulatum serotypes, but it also stained cultures of Blastomyces dermatitidis, H. duboisii, several Candida species, and a variety of other fungi. Adsorption of the conjugate with antigens of C. albicans produced a reagent that intensely stained only H. capsulatum, H. duboisii, and B. dermatitidis. Differentiation of B. dermatitidis from the Histoplasma species was accomplished by application of a B. dermatitidis specific fluorescent antibody to antigens positive with the H. capsulatum reagent. At present, differentiation of H. capsulatum from H. duboisii may be accomplished only by animal inoculation. Our data substantiate the antigenic relationships hypothesized earlier, and they indicate that H. capsulatum shares at least two antigens with the other fungi that were studied.